PKM Literasi Keuangan sebagai Fondasi Pengelolaan Usaha Peternakan Sapi Perah di Desa Pinang Kabupaten Enrekang - Indira Syakira Kirana Juanda; Endah Murpi Ningrum; Aini Indrijawati; Rahmawati HS; Muhammad Reza Pahlevi Juanda; Darmawati Darmawati (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
Dairy farming businesses in Enrekang Regency have significant economic potential to support food security and improve the welfare of rural communities. However, the low level of financial literacy among farmers remains a major obstacle to sustainable business management. This Community Service Activity (PKM) aims to improve dairy farmers' financial literacy, the foundation of effective, efficient, and sustainable business management. PKM implementation methods include counseling, training, mentoring, and direct practice to prepare simple financial records tailored to the characteristics of smallholder farming businesses. The activity results showed increased participants' understanding of basic financial literacy concepts, their ability to compile business cash flow records, and their awareness of the importance of financial planning and the separation of household and business finances. This activity is expected to strengthen dairy farmers' economic capacity and support the development of competitive, sustainable livestock businesses in Enrekang Regency.